Progression-Free and Overall Survival for Concurrent Nivolumab With Standard Concurrent Chemoradiotherapy in Locally Advanced Stage IIIA-B NSCLC: Results From the European Thoracic Oncology Platform NICOLAS Phase II Trial (European Thoracic Oncology Platform 6-14) - Peters, Solange; Felip, Enriqueta; Dafni, Urania; Tufman, Amanda; Guckenberger, Matthias; Álvarez, Ruth; Nadal, Ernest; Becker, Annemarie; Vees, Hansjörg; Pless, Miklos; Martinez-Marti, Alex; Lambrecht, Maarten; et al. (Journal of thoracic oncology, 2021)
The NICOLAS study is the first completed single-arm phase II trial in stage III NSCLC evaluating hierarchically first the safety and then the efficacy of adding nivolumab concurrently to standard definitive concurrent chemoradiotherapy. The safety end point was reported earlier; here, we present the efficacy results. Stage IIIA-B unresectable treatment-naive patients with NSCLC received three cycles of platinum-based chemotherapy and concurrent radiotherapy (66 Gy, 33 fractions), along with nivolumab (360 mg, 3-weekly). Nivolumab was continued as monotherapy consolidation for a maximum of 1 year (480 mg, 4-weekly). The primary end point was 1-year progression-free survival (PFS), with a target improvement compared with historical data of at least 15%, from 45% to 60%. To test this efficacy hypothesis, a sample size of 74 assessable patients provided a power of 83% with a one-sided alpha of 5%. A total of 79 patients were enrolled with a median follow-up of 21.0 months (interquartile range: 15.8–25.8 mo) for the primary PFS analysis. A total of 35.4% of the patients had stage IIIA, and 63.3% had stage IIIB disease. The 1-year PFS was 53.7% (95% confidence interval [CI]: 42.0%–64.0%) and the median PFS was 12.7 months (95% CI: 10.1–22.8 mo). Because 37 PFS events occurred in the first year posttreatment among the first 74 assessable patients, a 1-year PFS rate of at least 45% could not be rejected (p = 0.23). At an extended follow-up (median 32.6 mo), 37 deaths have been recorded, with a median overall survival (OS) of 38.8 months (95% CI: 26.8 mo–not estimable) and a 2-year OS rate of 63.7% (95% CI: 51.9%–73.4%). The OS of patients with stage IIIA disease was found to be significantly higher than patients with stage IIIB disease, with a 2-year OS of 81% and 56%, respectively (p = 0.037). PFS and OS are arithmetically higher in studies involving the same population. However, on the basis of the formal hierarchical efficacy analysis, we could not reject that the 1-year PFS rate is at least 45%.